Głos Wybrzeża dla Elbląga. (Gdańsk : [wydawca nieznany], 1949)
Afisz informujący elbląskim wydaniu Głosu Wybrzeża.
Keywords: Prasa -- Polska -- Lębork -- 1945-1970 -- druki ulotne; Lębork (Polska) -- 1945-1970 -- druki ulotne; Lębork (Polska) -- 1945-1970 -- źródła